Effects of different irrigation levels and nitrogen forms on yield, quality and water use efficiency of lettuce (International Journal of Irrigation and Water Management, 2014)
This study was conducted to investigate the effects of different irrigation levels and nitrogen forms on yield, quality and water use efficiency of lettuce (Lactuca sativa var. longifolia cv. Lital) under greenhouse conditions during the periods November 2003 - February 2004 in the Eastern Mediterranean region of Turkey. Four irrigation treatments with a drip irrigation system were based on adjustment coefficients (Kcp) (0, 0.75, 1.0, and 1.25) of Class A pan evaporation. Nitrogen (N) treatments were consisted of ammonium nitrate (NAN) and ammonium sulfate (NAS) forms. As the yield and quality parameters of plant; mean marketable head weight, number of total and marketable leaves, plant height and diameters, root wet weight, plant dry weight, core diameters and tightness of head were determined. N forms significantly affected plant diameter and number of total and marketable leaves. Yield and other yield components were not affected by different N forms. Irrigation levels had significant (p < 0.01) different effects on yield and yield components except for plant dry weight. The results showed that the highest yield was obtained from NANxKcp100 interaction plot. The water use efficiency (WUE) and the irrigation water use efficiency (IWUE) increased as the irrigation level reduced.